Preparation, in vitro Characterization and Pharmacokinetic Study of Coenzyme Q10 Long-Circulating Liposomes - Yang, Shuoye (Drug Research, 2018)
Long-circulating liposomal delivery systems of encapsulated Coenzyme Q10 (CoQ10), a ubiquinone anti-cataract agent, were developed with different molar ratios of PEGylated lipids and/or cholesterol. The resulting samples were contrasted through observation of morphology, analysis of particle size and Zeta potential, and in vivo pharmacokinetics. A protamine aggregation method with high selectivity was developed to determine the encapsulation efficiency (EE), after which the liposome formulation was further optimized by applying a Box Behnken design (BBD) using EE as the evaluation index. The results showed that liposomes had a large, unilamellar structure, and that particle sizes of cholesterol-containing liposomes increased along with the increase of cholesterol molar percentage, while the size of PEGylated vesicles decreased slightly as PEG-lipid contents increasing. The optimum formulation and optimal values of each influencing factor were quantitatively obtained, and the measured value was highly consistent with the predicted results. In vivo evaluation performed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) demonstrated that liposomal encapsulation largely prolonged half-lives and improved bioavailability for vectors prepared with either lipid component, and the liposomes composed of both cholesterol and PEG-lipid possessed the best pharmacokinetic properties. The results suggest that incorporating high contents of cholesterol and PEG modification could be a potentially useful method for enhancing the length of circulation and the sustained release effect for liposome-encapsulated chemicals.
Keywords: coenzyme Q10; long-circulating liposomes; encapsulation efficiency; response surface; pharmacokinetics